PEMBUATAN BIODIESEL DARI MINYAK DEDAK PADI DENGAN REAKSI TRANSESTERIFIKASI MENGGUNAKAN KATALIS HETEROGEN ZEOLIT ALAM YANG DIMODIFIKASI DENGAN KOH - Taslim, Sri Zahrani Dwi Mauliyah Parinduri, Putri Retno Wahyu Ningsih (Jurnal Teknik Kimia USU, 2017)
Biodiesel was usually produced from transesterification using alchohol. In this research rice bran oil was used as feedstock and methanol was used as reagent. The transesterification of rice bran oil had studied using KOH/natural zeolite as a solid heterogeneous catalyst. The objective of this study was to discover the effectivess of using natural zeolite modified by KOH as heterogeneous catalysts in the production of biodiesel from rice bran oil (RBO). KOH/natural zeolite catalyst was prepared by modification through impregnation method which was conducted on various KOH concentration (75 gram/100 ml – 175 gram/100 ml).  Transesterification reaction was conducted at 60 ºC, 500 rpm, and various amount of catalyst (2-4%), reaction time (1,5-3,5 hour) and molar ratio alcohol/oil (8:1-12:1). The highest yield of biodiesel was 98,71%, which was obtained by using 2% catalyst, reaction time 2 hour, molar ratio alcohol/oil 10:1. Natural zeolite as heterogeneous catalyst which modified by KOH could get the higher yield biodiesel on transesterification.